Character education and early childhood creativity strategies through educational games in Megamendung village - Rusdian Rifgiyansah; Akmal Rizki Gunawan; Yoyo Hambali; Siti Khadijah; Siti Yuliyati; Fika Diena Q; Didi Dito Laksono (Institut Studi Islam Muhammadiyah (ISIMU) Pacitan, 2023)
This dedication aims to emphasize the role of educators in shaping the character and creativity of early childhood. It goes beyond theoretical discussions during meetings or face-to-face classes, but involves active creation using instructional instruments and learning techniques that utilize direct teaching media. Innovation must be maximized as it can enhance children's reasoning abilities. All thoughts within teenagers can be created through creative activities. Creative activities provide valuable opportunities to express feelings and perspectives, fostering creativity in children. Educators are expected to continuously demonstrate innovative strategies. This technique brings children into active participation in learning cultivating their excellence effectively. The activity was carried out on July 15-16, 2023, at Camp Ground Lentemland, Curug Panjang Subdistrict, Bogor Regency, West Java, involving 20 elementary school children and 30 students from the Department of Islamic Education, 45 Islamic University, Bekasi. Based on the results of the dedication, it can be concluded that education strategies for the character of early childhood through learning while playing, engaging in learning activities, playing, and developing artistic souls can provide a new impression on children and enhance their creativity. Additionally, children begin to interact with their peers and accompanying students, creating a sense of enthusiasm and synergy